Atomistic simulation of helium diffusion and clustering in plutonium dioxide. Issue 35 (1st August 2022) - Murray, Elanor; Zhou, Ying; Slater, Peter; Smith, Roger; Goddard, Pooja; Steele, Helen
Abstract : Helium atoms diffuse via oxygen vacancies in PuO2 . Helium atoms will migrate to growing helium clusters, the maximum He : vacancy ratio of a stable helium cluster is approximately 3.5 : 1. Abstract : This study uses molecular dynamics and barrier searching methods to investigate the diffusion and clustering of helium in plutonium dioxide. Such fundamental understanding of helium behaviour is required because radiogenic helium generated from the alpha decay of Pu nuclei can accumulate over time and storage of spent nuclear fuel needs to be safe and secure. The results show that in perfect PuO2, interstitial He is not mobile over nanosecond time scales at temperatures below 1500 K with the lowest diffusion barrier being 2.4 eV. Above this temperature O vacancies can form and diffusion increases. The He diffusion barrier drops to 0.6 eV when oxygen vacancies are present. High temperature simulations show that the key He diffusion mechanism is oxygen vacancy assisted inter-site hopping rather than the direct path between adjacent interstitial sites. Unlike oxygen vacancies, plutonium vacancies act as helium traps. However, isolated substitutional He at Pu sites can be easily ejected through displacement by neighbouring interstitial Pu atoms. High temperature MD simulations show that helium can diffuse into clusters with the majority of helium clusters which form over nanosecond time scales having a He : vacancy ratio below 1 : 1. Further static calculations show that a ∼3.5 : 1 He : vacancy ratio is the largest possible for an energetically stable helium cluster. Schottky defects act as seed points for He cluster growth and a high local concentrations of He can create such defects which then pin the growing He cluster.